Geographies of oppression and resistance: Contesting the reproduction of the heterosexual regime - Grant, Ali (My University, 1996)
In this thesis I offer a specifically lesbian and geographic analysis of particular struggles for social change in Hamilton, Canada. Through an investigation of the deployment of the political regime of heterosexuality in the regulation and containment of local anti-violence activism in the 1990s, I build on emerging work in feminist, and lesbian and gay geographies on the institution of heterosexuality as regulatory. Through an exploration of both the struggles over the development of spaces of political resistance, and the importance of gender, sexuality, and "difference" in local urban politics, I suggest that "unnaturalizing" categories such as Woman/Man can offer insights to the processes of identity formation in place. Through employing a politically engaged methodology and constructing this research as part of local struggles for social change, I offer local activists critical analyses of political strategies and processes of institutionalization in Hamilton, as well as challenging the ongoing invisibility of lesbians in geography and beyond.
Keywords: Geography; Geography